Recurrent polychondritis: a review of the literature and a clinical case description - L. N. Denisov; I. B. Vinogradova; L. A. Bakhtina (Современная ревматология)
Relapsing polychondritis (RPC) is a rare disease, its diagnosis presents certain difficulties. This is due to the absence of characteristic clinical manifestations at the initial stages of the disease, late diagnosis and difficulties in selecting adequate therapy.The article presents a review of the literature on the diagnosis and treatment of RPC, as well as a clinical case with tracheobronchial tree and other organ systems involvement in the absence of classical auricular involvement.